Prospecting Endophytic Bacteria Endowed With Plant Growth Promoting Potential Isolated From Camellia sinensis - Hazarika, Shabiha Nudrat; Saikia, Kangkon; Borah, Atlanta; Thakur, Debajit (Frontiers in Microbiology, 2021)
Endophytes are well-acknowledged inoculants to promote plant growth and extensive research has been done in different plants. However, a lacuna determines the endophytes associated with tea clones and their benefit to promote plant growth. The present study focuses on isolating, and characterizing the beneficial endophytic bacteria (EnB) prevalent in commercially important tea clones cultivated in North Eastern India as plant growth promoters. Diversity of culturable EnB microbiome, in vitro traits for plant growth promotion (PGP), and applicability of potent isolates as bioinoculant for in vivo PGP abilities have been assessed in the present study. A total of 106 EnB identified as members of phyla Proteobacteria, Firmicutes and Actinobacteria were related to 22 different genera and six major clusters. Regarding PGP traits, the percentage of isolates positive for the production of indole acetic acid, phosphate solubilization, nitrogen fixation siderophore, ammonia, and 1-aminocyclopropane-1-carboxylic acid deaminase production were 86.8, 28.3, 78.3, 30.2, 95.3, and 87.7 respectively. In total, 34.0%, 52.8%, 17.0% of EnB showed notable production of hydrolytic enzymes like cellulase, protease, and amylase respectively. Additionally, based on the bonitur score, the top two isolates K96 identified as Stenotrophomonas sp. and M45 identified as Pseudomonas sp. were evaluated for biofilm formation, motility, and in vivo plant growth-promoting activity. Results suggested strong biofilm formation and motility in K96 and M45 which may attribute to the colonization of the strains in the plants. Further in vivo plant growth promotion experiment suggested sturdy efficacy of the K96 and M45 as plant growth promoters in nursery condition in commercial tea clones Tocklai vegetative (TV) TV22 and TV26. Thus, this study emphasizes the opportunity of commercialization of the selected isolates for the sustainable development of tea and other agricultural crops.